Impelementation of Kurikulum Merdeka (Freedom curriculum) in science learning: A case study in Sekolah Indonesia Kuala Lumpur, Malaysia - Nurdiyanti, Nurdiyanti; Wajdi, Muhammad; Magfirah, Nurul (Edelweiss Applied Science and Technology, 2024)
Many countries have focused on developing curricula that emphasize competencies within their educational frameworks. In Indonesia, schools have adopted the "Kurikulum Merdeka" (Freedom Curriculum), backed by government initiatives. Indonesian schools abroad have also implemented this curriculum, notably in Kuala Lumpur, Malaysia. This study investigates the implementation of the Kurikulum Merdeka (KM) at the Indonesian School Kuala Lumpur (SIKL), with a specific emphasis on science education. The Indonesian Ministry of Education and Culture developed KM, a novel curriculum that prioritizes the growth of students’ competencies and character. This research utilized a mixed-method approach, employing an explanatory sequential method, to collect and analyze both quantitative and qualitative data. The study involved 14 teachers representing various educational levels and subjects, including three dedicated to science. Findings revealed that 71.4% of teachers still needed to establish learning objectives; 64.3% had not created teaching modules; and all used electronic teaching materials. Furthermore, 92.9% participated in P5 activities, albeit not always as implementers, and 42.9% faced difficulties in grasping the concept and execution of P5. Qualitative analysis indicated that all science teachers had integrated the Kurikulum Merdeka into their teaching processes. However, they encountered challenges such as generating teaching ideas, the high cost of project implementation, diverse student abilities, and limited resources.